Scattered trees across rangeland landscape in Senegal provide shade for livestock - Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2024)
image shows the role of the trees in Senegal rangelands serving as crucial providers of shade, offering relief and protection to grazing livestock from the scorching sun